Ethnobotany of traditional wedding: a comparison of plants used by Bugis, Palembang, Sundanese and Karo ethnic in Indonesia. (March 2019) - Rasdianah Aziz, Isna; Restu Puji Raharjeng, Anita; Susilo,; Nasution, Jamilah
Abstract: Various ethnic in Indonesia including Bugis, Palembang, Sundanese and Karo utilize plants species in their traditional wedding processions as a science of ethnobotany. This study aims to identify and compare the most widely used plant species, the parts of the organ used, and their meaning. The method used is descriptive explorative through semi-structured interviews using open-ended question. The results show there are four plants of same species that most widely used by the four ethnic groups: Piper betle, Oryza sativa, Pandanus amaryllifolius and Musa sp. in every traditional wedding processions. Ethnic communities still cultivate these plants to prevent extinction in their regions.